Prototype Lengan Robot Pemilah Sampah Organik dan Anorganik - Eno Febra Wardani; Nelly Khairani Daulay; Muhammad Nur Alamsyah (STMIK Budi Darma, 2023)
Along with the times like today, with the existence of technology, public awareness of environmental cleanliness is very low, especially for disposing of garbage. But thanks to advances in science and technology, it can encourage people to overcome the various problems they face. One of them is microcontroller technology which plays an important role in the field of human life. There is a package of robots with these four functions, namely, line-following robots, tracker robots, arm robots and waste sorting robots as organic and inorganic waste sorting robots, so as to reduce the accumulation of waste in the room. With this robot, the work of conventional garbage collection by humans can be lighter, of course, more accurate, especially in separating two types of waste, namely organic and inorganic types of waste. The purpose of this research is to design and build a package of robots with four functions namely, line following robot, tracker robot, arm robot and waste sorting robot. Which later can work as a robot sorting organic and inorganic waste. So that it can reduce the accumulation of garbage in the room. The results of testing the HCSR04 sensor can detect less than 10cm, Inductive Proximity sensors can detect less than 2mm, Capacitive Proximity sensors can detect less than 4 mm, testing 4 Servo Motors can function properly in one circuit, and testing DC Motor works in supply voltage 9v normally